Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Jambi Timur Kota Jambi - Muhammad Emil; Erwin DS (J-MAS (Jurnal Manajemen dan Sains), 2021)
In carrying out organizational activities, the work environment is all conditions that are around workers, so that either directly or indirectly it can influence in carrying out assigned tasks. The method of collecting data in this study uses library research and field research by collecting data from a list of statements. And information that comes from books and the internet for theory making. Subdistrict Jambi Timur Kota Jambi is an arean was established on 8 November 2006 based on the regional Number 12 in 2006. Dubdistrict Jambi Timur Kota Jambi Capital City Tanjung Pinang. Based on the research results, the simple regression value is Y = 0.785 + 0.669 X, with an R value and a R2 value of 0.496. In the t test, the work environment affects the performance of employees at the Head Office of East Jambi, Jambi City with a tcount of 7.809 and a significant value of 0.000. Suggestions in this study are Jambi to pay attention to the work environment in the East Jambi Sub-district Office of Jambi City related to sound / noise. As employees of the sub-district office, we should pay attention to performance related to communication between colleagues.